0739 Efficacy and Safety of AXS-12 in the Treatment of Narcolepsy: Results from a Phase 2, Double-Blind, Placebo-Controlled, Crossover Trial. (27th May 2020) - O'Gorman, C; Jones, A; Thorpy, M J; Tabuteau, H
Abstract: Introduction: Narcolepsy is a chronic, debilitating, neurological disease characterized by excessive daytime sleepiness (EDS), cataplexy, and sleep-wake dysregulation. Existing treatments are limited, provide variable efficacy, and have significant tolerability issues. AXS-12 (reboxetine) is a potent, and highly selective norepinephrine reuptake inhibitor with potential for therapeutic differentiation in narcolepsy. Methods: The CONCERT study was a Phase 2, double-blind, randomized, placebo-controlled, crossover trial of AXS-12 in narcolepsy subjects exhibiting moderate and severe symptoms of cataplexy and EDS. Subjects were randomized (1:1) to treatment with AXS-12 followed by placebo, or placebo followed by AXS-12. AXS-12 dosing was 8mg/day for week 1, escalated to 10mg/day for week 2. Crossover occurred after a one-week down-titration/washout. The primary endpoint was the change in weekly cataplexy attacks from baseline, averaged over the 2-week treatment period for overall treatment effect. Secondary endpoints included improvements in EDS, cognitive function, sleep quality and sleep-related symptoms. Results: Twenty-one subjects were randomized. The baseline mean weekly number of cataplexy attacks was 30.0 and mean ESS score was 18.1, reflecting moderate and severe illness on both core symptoms. AXS-12 met the prespecified primary endpoint, demonstrating a statistically significantly greater reduction in the mean number of weekly cataplexy attacks (-13.0 with AXS-12 vs -0.3 with placebo; p<0.001) over 2 weeks of treatment. Statistically significant reductions in EDS were observed for AXS-12 compared to placebo, assessed by changes in the Epworth Sleepiness Scale (-6.0 vs -3.1; p=0.003), number of weekly inadvertent naps (-5.88 vs -0.98; p<0.001). AXS-12 was associated with improved cognitive function (p<0.002) and sleep quality (p<0.007), and reduced night awakenings (p<0.05). Rapidity of effect was observed with significant symptomatic improvements occurring as early as week 1 starting at the lower 8mg dose. AXS-12 was safe and well-tolerated with no serious adverse events or discontinuations due to adverse events. Conclusion: AXS-12 is a novel approach for the treatment of narcolepsy with the potential for comprehensive clinical symptom management compared to current treatments. In this Phase 2 study, AXS-12 resulted in statistically significant improvements in cataplexy, excessive sleepiness, cognitive function and night awakenings in patients with narcolepsy with a favorable safety profile. Support: Axsome Therapeutics.